Thomas Aquinas, sj: A Thomistic Analysis of Ignatian Consolation and Desolation - Bishop, John (Toronto journal of theology, 2016)
In this article, we give a Thomistic analysis of Ignatian consolation and desolation as they are found in Ignatius of Loyola's Spiritual Exercises. Specifically, we show that Aquinas's explanation of peace, joy, and discord in his discussion of charity provides an appropriate lens through which we can view Ignatian consolation and desolation. Further, we argue that consolation should be understood as a combination of Aquinas's spiritual peace and spiritual joy, and that this understanding helps to clarify Ignatian consolation, particularly with regard to determining whether causes of consolation without previous cause are genuine or not.